INFLUENCE ON HOMEOSTASIS AS THE CRITERION FOR SELECTING SINGLE NUCLEOTIDE POLYMORPHISMS FOR THE STUDY OF METABOLIC SYNDROM IN THE KAZAKH POPULATION - Benberin V.V.,; Voshchenkova T.A.,; Nagimtayeva A.A.,; Sibagatova A.S.,; Akhmetova K.M.,; Makhmutova A.N., (Academic Journal of Physical and Chemical Sciences, 2020)
Metabolic syndrome (MS) is increasingly cited as the world's leading health risk. The sequence of events toward multimorbidity in most cases passes through MS. According to the research, MS heritability ranges from 23 to 27% in Europeans, and 51 to 60% in Asians. The purpose of the review: to form a strategy for the selection of single nucleotide polymorphisms (SNPs) for the study of MS in the Kazakh population based on the effect of SNPs on homeostasis indicators The stable symptom complex of MS is a complicated dynamic system of successive accumulations of dysmetabolic disorders of homeostasis. This system starts the development of subsequent age-associated diseases), such as cardiometabolic, neurodegenerative, and malignant neoplasms. The system for selecting SNPs for the MS study, proposed on the basis of the concept of homeostasis dysfunction, assumes, in conditions of limited resources, to see the greatest level of their influence within the conditional framework of three genetic models of homeostasis dysregulation: insulin resistance , oxidative stress, and chronic inflammation. This approach is fundamentally different from the traditional approach involving candidate genes. It is expected that scientific research in this direction will contribute not only to the understanding of general biological processes, but also to the targeted search for genetic determinants and for new opportunities for personalized interventions.